Attempted Self-Harm with Elemental Thallium Purchased Online: Case Report with Analytical Confirmation - Anthony Spadaro; Andrew Sae Young Lee; Hilda Pineda; Bruce Ruck; Diane P. Calello; Howard A. Greller; Lewis S. Nelson; Mehruba A. Parris (Journal of Medical Toxicology, 2024)
Introduction Thallium is a highly toxic metal, with most publications demonstrating poisoning from thallium salts. We report on a patient with elevated serum and urine thallium concentrations from an intentional ingestion of elemental thallium purchased from the internet for self-harm. Case Report The regional poison center was contacted about an 18-year-old man who ingested a fragment from a 100-gram bar reported to be elemental thallium. Serial serum and urine thallium concentrations were obtained. Prussian blue was started on hospital day (HD) 2. A metal fragment was seen on abdominal x-ray and removed via colonoscopy on HD3. The ingested fragment was analyzed via inductively coupled plasma mass spectrometry (ICP-MS) and found to be 87.0% elemental thallium. The initial serum thallium concentration obtained on HD1 was 423.5 mcg/L (reference range < 5.1 mcg/L), which subsequently decreased to 4.5 mcg/L, 29 days after the ingestion. An initial random urine thallium concentration obtained on HD 3 was 1850.5 mcg/g creatinine (reference range < 0.4 mcg/g creatinine). The patient remained hospitalized for 23 days and, when seen in follow-up, had not developed any signs or symptoms of thallium toxicity. Discussion Elemental thallium ingestion is a rare toxicologic exposure, with limited published clinical and analytical experience to guide management. This case report describes a patient with ingestion of elemental thallium who developed elevated serum and urine thallium concentrations and was treated with Prussian blue. Despite having elevated serum and urine thallium concentrations consistent with previous fatal exposures, more evidence is needed to understand the differences between elemental thallium and thallium salts.